The Effect of a Corrective Exercise Program Based on Scapula Stability on Scapular Upward Rotation and Scapulohumeral Rhythm in Wheelchair Basketball Athletes With Bilateral Scapula Rotational Syndrome - Ahmad Ebrahimi Atri; Hasan Daneshmandi; Ali Asghar Norasteh; Abdollah Maarouf (University of Social Welfare and Rehabilitation Sciences, 2021)
Objective The present study aimed to investigate the effect of scapular stability-based corrective exercise program on scapular upward rotation and scapulohumeral rhythm in Wheelchair Basketball (WB) players with bilateral scapular downward rotation syndrome. Materials & Methods: According to the research conditions, 24 wheelchair basketball athletes with spinal cord injury voluntarily participated in this study. Initially, eight players were selected from each sport class (1 to 1.5 class, 2 to 2.5 class, and 3 to 4.5 class). Then, four subjects in each group were randomly assigned to each group (12 control subjects with Mean±SD age of 43.23±11.0 years and 12 experimental subjects with Mean±SD age of 39.08±5.08 years). Thus, the control and experimental groups were present in an equal number of three sport classes. WB athletes were professional players in Mashhad City league, Iran. The participants were classified according to the Classification Committee of the IWBF, as well as the corresponding national classification from the Islamic Republic of Iran Sports Federation for the Disabled (IRISFD). Two digital inclinometers were used to measure the humeral range of motion and scapular upward rotation and scapulohumeral rhythm in resting position, 45°, 90°, and 135° shoulder abduction in scaption plane. The exercise group performed scapular stability-based corrective exercises based on the Gym training principles and following ACSM guidelines for eight weeks. The independent t-test, analysis of variance, and analysis of covariance were used for statistical analysis at the significant level of less or equal to 0.05. Results: The results showed no significant asymmetry between dominant and non-dominant shoulders in the scapula's upward rotation at different angles of shoulder abduction. Contrary to the non-dominant shoulder, the dominant shoulder's scapula had a less downward rotation at the resting position and a higher upward rotation at 45° of shoulder abduction. Also, in 45° humeral abduction, the dominant shoulder has a less scapulohumeral rhythm ratio than the non-dominant shoulder. WB athletes' dominant shoulders in lower classes (2-2.5 and 3-4.5) have less scapular downward rotation in scapular resting position and more scapular upward rotation in 45°, 90° 135° humeral abduction. There was no significant difference in scapulohumeral rhythm ratio between WB players with different classes. Scapular upward rotation increased significantly after eight weeks of scapular stability-based corrective exercise program (P≤0.05). Also, a significant decrease in the scapular upward rotation was observed at post-program in resting position (P=0.001) and significantly increased in 45° (P=0.01), 90° (P=0.001), and 135° (P=0.001) humeral abduction compared with pre-program in dominant and non-dominant shoulders. However, the ratio of scapulohumeral rhythm in the dominant shoulder did not improve significantly, and the ratio of scapulohumeral rhythm in the non-dominant shoulder improved at 90° and 135°. Conclusion: Scapular stability-based corrective exercises can be used as one of the training methods to restore muscle balance, prevent and correct scapular upward rotation and scapulohumeral rhythm in wheelchair basketball athletes. Therapists should know that some degrees of scapular upward rotation and scapulohumeral rhythm asymmetry may be common in WB players. This asymmetry should not always be considered a pathological symptom but may be an adaptation to exercise training and frequent use of the upper extremity.